Pembinaan Manusia Usia Dewasa dan Lanjut di Pesantren Daarut Tauhid Bandung (Human Development Among Adult and Old People at the Daarut Tauhid Islamic Boarding School in Bandung) - Sitti Chadidjah; Andewi Suhartini; Ahmad Nur Wajah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
There are very few Islamic boarding schools (pesantren) that focus on adult and elderly religious education. Whereas adult humans and elderly are thirsty and need religious education.The aim of this research is to delve the concept of Islamic education for adults and elderly and its implementation in Pesantren Darut Tauhid. The research method used qualitative approach, which describes the role of pesantren in responding to the needs of adult and elderly beings to equip their personal lives and prepare themselves to return to Him. Darut Tauhid provides a solution through the Golden Islamic Boarding School Program. The material presented was from daily worship to role play in the grave that was played by the participants. This method is following by Knowles where adults prefer to learn based on needs, life experience, hands-on practice, and carry out social activities of interest.